The Relationship Between Student Participation and Gender Stereotypes In Physical Education Subjects At State Junior High School 1 Hulu Sungai Tengah - Nur Aisyah; Lazuardy Akbar Fauzan; Nurdiansyah (Universitas Negeri Semarang, 2025)
This study aims to analyze the relationship between gender stereotypes and student participation in physical education subjects at state junior high school 1 Hulu Sungai Tengah.The method used is correlational research with a quantitative approach. The research sample consisted of 72 female students in grades 7 to 9, who were selected using the Slovin formula. Data was collected through a closed questionnaire based on the Likert scale, this questionnaire consisted of 35 statements, which included 22 positive statements and 13 negative statements that had been tested for validity and reliability. Data analysis used the Pearson Product Moment correlation test. The results showed a significant relationship between gender stereotypes and female student participation in physical education subjects, with a correlation coefficient value of 0.463 > a table of 0.229. Strong gender stereotypes contribute to low female participation in certain physical activities, especially big ball games. The conclusion of this study emphasizes the need for teachers to design a more inclusive and gender-sensitive sports learning strategy to increase student involvement in physical education learning subjects so that the lack of student participation can be overcome.